N-type organic electrochemical transistors with stability in water - Giovannitti,A; nielsen,CN; Sbircea,DTS; Inal,SI; Donahue,MD; Niazi,MN; Hanifi,DH; Amassian,AA; Malliaras,GGM; Rivnay,JR; McCulloch,IM (Nature Communications, 2016)
Organic electrochemical transistors (OECTs) are receiving significant attention due to their ability to efficiently transduce biological signals. A major limitation of this technology is that only p-type materials have been reported, which precludes the development of complementary circuits, and limits sensor technologies. Here, we report the first ever n-type OECT, with relatively balanced ambipolar charge transport characteristics based on a polymer that supports both hole and electron transport along its backbone when doped through an aqueous electrolyte and in the presence of oxygen. This new semiconducting polymer is designed specifically to facilitate ion transport and promote electrochemical doping. Stability measurements in water show no degradation when tested for 2 h under continuous cycling. This demonstration opens the possibility to develop complementary circuits based on OECTs and to improve the sophistication of bioelectronic devices.